Nuevas formas de comunicación e integración entre jóvenes a través de Facbook. - Donoso Alarcón, Pamela Patricia (2016)
This study is conducted in the framework of communication with a sociocultural approach. The introduction talks about human relationships and how their roles change with the advent of social networks. For which analysis work performed previously studied and related to this study. qualitative methodology is used allowing compression system in which the communication established among adolescents, through smilies develops. For the analysis of the study to two pairs of adolescents 13 to 15 years, choosing subjects for their characteristics and the information they can provide, their participation is chosen to be necessary. The central idea is to focus on four minors, at the beginning of their love affair and communication through chat called "Messenger" on the Facebook platform using emoticons, the research question states: what they are the main consequences in communication and expression of these individuals by using chat and instant messaging? Is it possible to keep more expressive virtual and face less expressive? It is mainly concludes that the use of smilies in the process of infatuation among adolescents study increases by two factors: the affiliation of young people in technology by providing better access in real time with a greater number of people and the dynamism of modern society which it requires agile communications media and easily understood.